Trade policy in Asia: Where next with a crippled WTO and weak FTAs? - Razeen Sally (European Centre for International Political Economy (ECIPE), 2007)
Trade policy in Asia is dangerously unbalanced. It rests on a shaky leg of discriminatory bilateral and regional FTAs. Its other WTO leg has gone to sleep: most Asian countries have neglected the WTO in favour of FTAs. Its regional-cooperation arm is limp: grand visions for regional economic integration are mostly empty conference chatter. Above all, core abdominal strength through unilateral liberalisation and pro-market domestic reforms has weakened post-Asian crisis. China is the conspicuous exception. Now, after the collapse of the Doha round and a fraying multilateral trading system, three priorities are called for. First, a clutch of East-Asian countries plus India should be active in "coalitions of the willing" to set the WTO on its legs again. US leadership and a Chinese helping hand will be crucial. Second, existing FTAs should be cleaned up and new FTA initiatives only launched with caution and a sense of economic strategy. Third, and most important, it is vital that the engine of Chinese unilateral liberalization does not stall. That is the only major route to further liberalization and regulatory reform across Asia and beyond - through competitive emulation, not trade negotiations.
Keywords: 330; Außenwirtschaftspolitik; WTO-Mitgliedschaft; Freihandelszone; Asien